Optimizing the Surgical Field via Multimodal Controlled Hypotension during Posterior Spinal Fixation for a T11 Burst Fracture: An Anesthetic Case Study - Juliana; Heri Dwi Purnomo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Significant intraoperative blood loss is a major challenge in complex spinal surgeries, impairing surgical field visibility and increasing patient morbidity. Controlled hypotension is an established anesthetic technique to mitigate this challenge, yet the optimal combination of agents to ensure efficacy and safety remains an area of active investigation. This case study details the successful application of a multimodal anesthetic regimen, centered on the synergistic effects of dexmedetomidine and isoflurane, to achieve deliberate hypotension during posterior stabilization of a thoracic burst fracture. Case presentation: A 39-year-old male, classified as American Society of Anesthesiologists (ASA) physical status II, presented with a traumatic, unstable burst fracture of the eleventh thoracic vertebra (T11) following a high-energy fall. He was scheduled for a posterior decompressive laminectomy and T10-T12 pedicle screw fixation. Anesthetic management was initiated with a multimodal approach utilizing intravenous infusions of dexmedetomidine and morphine, supplemented by maintenance with isoflurane. This strategy was employed to maintain a target mean arterial pressure (MAP) of 60-65 mmHg. Throughout the 135-minute procedure, the patient’s hemodynamics remained exceptionally stable within the target range. The estimated blood loss was minimal (approximately 350 mL), providing the surgical team with an excellent, clear operative field. The patient emerged smoothly from anesthesia with no neurological deficits and experienced a favorable postoperative recovery. Conclusion: This case demonstrates that a multimodal anesthetic strategy incorporating dexmedetomidine, a volatile agent, and opioid infusions is a highly effective and safe method for inducing and maintaining controlled hypotension in major spinal surgery. This approach successfully optimized the surgical conditions by minimizing blood loss and enhancing visibility, without compromising hemodynamic stability or vital organ perfusion, thereby contributing to a positive patient outcome.